2022
DOI: 10.1186/s13148-022-01241-7
|View full text |Cite
|
Sign up to set email alerts
|

The applications of DNA methylation as a biomarker in kidney transplantation: a systematic review

Abstract: Background Although kidney transplantation improves patient survival and quality of life, long-term results are hampered by both immune- and non-immune-mediated complications. Current biomarkers of post-transplant complications, such as allograft rejection, chronic renal allograft dysfunction, and cutaneous squamous cell carcinoma, have a suboptimal predictive value. DNA methylation is an epigenetic modification that directly affects gene expression and plays an important role in processes such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 139 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Although our study focused only on the four fundamental pillars, other omics technologies exist. These other omics, including epigenomic, fluxomic, inomic, or lipidomic, could bring a novel perspective to the field of transplantation [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study focused only on the four fundamental pillars, other omics technologies exist. These other omics, including epigenomic, fluxomic, inomic, or lipidomic, could bring a novel perspective to the field of transplantation [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few current convincing studies identified cell-free DNA (circulating/donor-derived) as well as EVs, specifically kidneyspecific parameters (aquaporin, CD133, clusterin, PODXL, SYT17 as well as multiple mRNA signatures), as promising markers for early graft dysfunction in several clinical KTA settings [54,55]. Notably, in the field of genomic and transcriptomic profiling, the assessment of DNA methylation seems to become a potential new and sensitive clinical biomarker in the detection of early graft dysfunction during KTA and consecutively targeting therapy for the future [58]. However, further research is needed to evaluate the significance of these new approaches for early graft dysfunction in SPKT, with the pancreas-specific lipase and alterations of CRP being by far the most specific IRI and graft dysfunction markers for the pancreas graft yet.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL-10. It is a chemokine secreted by renal graft leukocytes that regulate angiogenesis in conditions such as wound healing, ischemia and neoplasia [ 37 ]. It is also a sign of inflammation.…”
Section: Serological and Urine Biomarkersmentioning
confidence: 99%
“…It is also a sign of inflammation. CXCL-10 (uCXCL-10) in urine appears to be more sensitive and specific than creatinine in serum [ 37 ]. Its levels can aid in the detection of early signs of acute renal failure as well as the diagnosis of noninvasive kidney disease [ 38 ].…”
Section: Serological and Urine Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation